Optimizing Sn doping in Zn4Sb3 thin films: insights into processing and electrical performance - Chen, Cheng-Lung; Tang, Bo-Chen; Chen, Sheng-Chi; Wen, Chao-Kuang; Chen, Yin-Hung; Nor Hairin, Assayidatul Laila (Chemistry Europe, John Wiley & Sons, 2025)
β-Zn4Sb3 is a promising thermoelectric material due to its environmental friendliness and suitability for mid-temperature applications which aligns with the development of renewable energy. However, maintaining its pure β-phase during fabrication remains a significant challenge, as phase instabilities often degrade its thermoelectric performance. Here, we demonstrate the successful optimization of β-Zn4Sb3 thin films through controlled Sn doping using ion beam-assisted deposition. By precisely regulating the Sn concentration at 0.97 %, the β- Zn4Sb3 phase is preserved, resulting in a maximum power factor of 1.4 mWm- 1K- 2 at 573 K—a 60% improvement over undoped films. Comprehensive analyses reveal that dilute Sn doping enhances carrier mobility and structural stability while avoiding detrimental phase transitions to ZnSb. These findings highlight the importance of precise doping and processing control in stabilizing the β-phase structure. This work provides a new pathway for fabricating high-quality thermoelectric thin films, offering valuable insights into the development of scalable, efficient energy harvesting technologies.